GENOTYPE × ENVIRONMENT INTERACTION OF CORM AND CORMEL PRODUCTION IN GLADIOLUS - TANYA THAKUR,; K. K. DHATT, (The Bioscan, 2015)
Twelve gladiolus genotypes were planted on five different dates from 10th October to 10th December, 2011 at fortnightly interval and traits for corm and cormel production were evaluated. The number of corms and cormels per plant were maximum under 10th October planting (1.75 and 24.37 respectively) and in cv. Punjab Lemon Delight (2.01) and Punjab Glance (41.52) respectively. The result of G x E interaction shows that the number of corms and cormels per plant in twelve genotypes under five different environments ranges from 1.00 to 2.66 and 1.66 to 75.00 respectively. The maximum corm weight and corm size was in cv. Rose Supreme (102.70 g and 5.66 cm respectively) and under 10th October planting (76.07g and 4.39cm respectively). The G x E interactions shows that the corm weight per plant and corm size ranges from 10.83 to 106.86g and 2.70 to 6.51cm respectively. It concluded that the best planting time with respect to corm and cormel production was 10th October while 10th December was least favourable.